Single-Cell Elemental Analysis of Bacteria: Quantitative Analysis of Polyphosphates in Mycobacterium tuberculosis - Talaat, Adel M. (Frontiers in Cellular and Infection Microbiology, 2012)
More than 1.8 million people die annually from infection with Mycobacterium tuberculosis, the causative agent of tuberculosis. The ability of M. tuberculosis to obtain and distribute micronutrients, including biometals, is known to play a role in its intracellular survival and virulence within a host. Techniques to detect elemental distributions within M. tuberculosis cells have previously been limited to bulk detection methods or low-resolution analyses. Here, we present a method for determining the elemental distribution within M. tuberculosis on a single-cell level, at high (individual nanometer) resolution, using scanning transmission electron microscopy (STEM) in concert with energy-dispersive X-ray spectroscopy (EDS). Results revealed the presence of large polyphosphate granules in all strains of Mycobacteria tested. These persisted even through starvation conditions, and might play a role connected to elemental homeostasis in M. tuberculosis. Associated with the polyphosphate granules were micronutrients such as calcium and magnesium. In addition, we expanded the technique beyond Mycobacteria to show that STEM and EDS could be used as a simple screen to detect the presence or absence of concentrated elements on a single-cell level within all six other bacterial types tested, with minimal processing to the bacteria. Overall, we believe that this technique represents a first step in developing a better understanding of the role that components of the intracellular milieu, including polyphosphates and biometals, play in the pathogenesis of M. tuberculosis, with potential future applications for in vivo analysis.